Role of strawberry volatile organic compounds in the development of Botrytis cinerea infection. (19th September 2014) - Neri, F.; Cappellin, L.; Spadoni, A.; Cameldi, I.; Algarra Alarcon, A.; Aprea, E.; Romano, A.; Gasperi, F.; Biasioli, F.
<x xml:space="preserve">Abstract</x> Botrytis cinerea, the main pathogen of strawberry, has the ability to remain quiescent in unripe tissue and develop disease symptoms in ripe fruit. As strawberry ripening is characterized by an increase of aroma compounds, the role of volatile emission in the development of infection was investigated. Thirty‐five strawberry volatile organic compounds (VOCs) were tested on B. cinerea in vitro and volatile emission was analysed in strawberry harvested at four ripening stages by headspace solid‐phase microextraction/gas chromatography–mass spectrometry and proton transfer reaction–time of flight–mass spectrometry. The coupling of such data sets made it possible to conclude that key strawberry aroma compounds stimulate B. cinerea conidial germination and some typical wound‐volatiles stimulate pathogen conidial germination or mycelial growth. This study is the first report of fungal stimulation by some VOCs naturally occurring in strawberry: the esters ethyl butanoate, cis‐3‐hexenyl acetate, trans‐2‐hexenyl acetate, methyl butanoate and hexyl butanoate, the furanones furaneol and mesifurane, and the alcohol trans‐2‐hexenol. The results of this work provide advances in understanding the functional role of fruit VOCs and suggest, for the first time, that fruit VOCs may influence the development of B. cinerea from the latent phase and that they could favour the invasive growth of B. cinerea after wounding. In particular, ethyl butanoate and furaneol could signal strawberry ripening, and the green leaf volatiles trans‐2‐hexenol, trans‐2‐hexenyl acetate and cis‐3‐hexenyl acetate could signal the presence of damaged tissues that are easier sites for penetration by B. cinerea.